A Prospective Randomized Study Comparing the Interference Screw and Suture Anchor Techniques for Biceps Tenodesis. (February 2017) - Park, Ji Soon; Kim, Sae Hoon; Jung, Ho Jin; Lee, Ye Hyun; Oh, Joo Han
Background: Several methods are used to perform biceps tenodesis in patients with superior labrum-biceps complex (SLBC) lesions accompanied by a rotator cuff tear. However, limited clinical data are available regarding the best technique in terms of clinical and anatomic outcomes. Purpose: To compare the clinical and anatomic outcomes of the interference screw (IS) and suture anchor (SA) fixation techniques for biceps tenodesis performed along with arthroscopic rotator cuff repair. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: A total of 80 patients who underwent arthroscopic rotator cuff repair with SLBC lesions were prospectively enrolled and randomly divided according to the tenodesis method: the IS and SA groups. Functional outcomes were evaluated with the visual analog scale (VAS) for pain, American Shoulder and Elbow Surgeons (ASES) score, Simple Shoulder Test (SST), Constant score, Korean Shoulder Score (KSS), and long head of the biceps (LHB) score at least 2 years after surgery. The anatomic status of tenodesis was estimated using magnetic resonance imaging or ultrasonography, and the anatomic failure of tenodesis was determined when the biceps tendon was not traced in the intertubercular groove directly from the insertion site of the IS or SA. Results: Thirty-three patients in the IS group and 34 in the SA group were monitored for more than 2 years. All postoperative functional scores improved significantly compared with the preoperative scores (all P < .001) and were not significantly different between the groups, including the LHB score (all P > .05). Nine anatomic failures of tenodesis were observed: 7 in the IS group and 2 in the SA group ( P = .083). In a multivariate analysis using logistic regression, IS fixation ( P = .003) and a higher (ie, more physically demanding) work level ( P = .022) were factors associated with the anatomic failure of tenodesis significantly. In patients with tenodesis failure, the LHB score ( P = .049) and the degree of Popeye deformity by the patient and examiner ( P = .004 and .018, respectively) were statistically different compared with patients with intact tenodeses. Conclusion: Care must be taken while performing biceps tenodesis in patients with a higher work level; IS fixation appears to pose a higher risk in terms of the anatomic failure of tenodesis than SA fixation, although functional outcomes were not different.